Synergistic interaction between chemotherapeutic analogues and chloroform fruit extract of Acacia arabica (L.) willd var. indica against enterotoxigenic Escherichia coli - M.G. Roymon, *Deboshree Biswas and (International Multidisciplinary Research Journal, 2011)
Diarrheal infections caused by MDR E. coli have been recognized as one of the most serious health problems. Bioactive principles present in plant extracts has ability to sensitize chemotherapeutic analogues which gets completely ineffective against pathogen. Synergistic interaction between chloroform fruit extract of Acacia arabica Lam. Willd var indica and five different chemotherapeutic analogues (Tetracycline, Erythromycin, Chloramphenicol, Ampicillin and Penicillin G) provides a promising approach for treatment of diarrheal infection associated with enterotoxigenic E. coli. In vitro synergistic efficacy between plant extracts and antibiotics were performed by well-diffusion method. Results showed that interaction between chloroform fruit extract/tetracycline, chloroform fruit extract/erythromycin and chloroform fruit extract/chloramphenicol were synergistic and additive however combinations between plant extracts and ampicillin showed no synergistic effect against ETEC (Standard) strain. Synergism was also not observed on concurrent administration between extract and penicillin G against ETEC (Environmental isolate). Despite of two negative results clear synergistic/additive interaction was verified in all combinations used against tested organism.